PARADIGM OF MUHAMMADIYAH CADRE EDUCATION: Study of Cadre Education in M. Din Syamsuddin’s Leadership (2005-2015) - Arifah Cahyo Andini Suparmun (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2019)
Since its early establishment, Muhammadiyah situates cadres education as major and strategic programs and activities to prepare successors who area superior, competitive, and loyal as well as who have steadfast in the faith and tawhid. is an effort so as Muhammadiyah will be ready to face the challenges of the modern- world and the future. this present study aimed to describe the dynamics and style of cadre education of Muhammadiyah under the leadership of the Din Syamsuddin. Data collection techniques in this research are in-depth interviews, documentation, and triangulation. A qualitative research approach is used, specifically, descriptive-analytical methods, examine the natural objective conditions in which researchers serve as the key instrument. The data analyzed inductively.The results of this study indicate that the cadre education of Muhammadiyah in 2005-2015 is carried out continuously is through the revitalization of cadres and members of Muhammadiyah. It involves the establishment, development, improvement, and extensification of the core members. is achieved through the establishment of ideological formulations (the SPM 2007 and SPM 2015) as the response to the deterioration, of values, as well as identity, and self-confidence crisis in the levels of leadership, cadre, and community of Muhammadiyah. Nevertheless, 2005-2015, the movements became more progressive. This is evident from the development of cadre education of Muhammadiyah which system is more flexible, open-minded, independent, and innovative in line with scientific progress and social changes. In addition, other features also contribute to strengthening the synergy of Muhammadiyah cadres.